Analisis Perilaku Pemilih pada Pemilihan Gubernur DKI Jakarta Periode 2012-2017 - Martinus, Handy (Bina Nusantara University, 2013)
This research is an exploratory qualitative approach using secondary data from the Indonesian Survey Institute (LSI), which aims to identify the voters’ behavior of Jakarta Governor candidates period 2012-2017. The results showed that the implementation of the election was considered by the respondents Honest-Fair (JURDIL) and quite satisfying. The selection was won by Joko Widodo – Basuki Tjahaja Purnama. However, the numbers did not reach half of the voters. Therefore, the election took 2 rounds. For Governor-Vice Governor couples socialization, both the majority and not overtaken, Fauzi Bowo – Nachrowi achieved top ranking with very significant. But apparently, successful socialization of media did not match with the victory in the election. This study aims to determine the behavior of voters in Jakarta governor election. The result, in contrary, shows that the couple in number two socialization won the election. For the popularity, it was not in tune with the socialization. Personally, the popularity of Joko Widodo topped more than the incumbent. It is believed that the performance and imaging of Joko Widodo as mayor of Solo viewed favorably by the public. Close relationship with lower level people and hawkers handling gained the voters’ sympathy. Regarding the evaluation of the incumbent, the majority responded quite satisfied because they could understand the complexity of the Jakarta capital region. But ironically, the majority answered there is no change during the leadership of the incumbent governor. Voters preference based on gender, religion, ethnicity, and age in majority chose the couple of Joko Widodo – Tjahaja Basuki Purnama.